Evaluation of New Grape Hybrids and French Cultivars for Wine Production - K Ranjitha (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2014)
This study aimed at evaluating newly developed hybrids and recently introduced cultivars of French grapes grown in mild tropics of South India for quality wine production. Wines produced from French grapes, viz., Cabernet Sauvignon, Shiraz, Pinot Noir, Sauvignon Blanc, Chenin Blanc and Ugni Blanc scored 15.0 -16.8 in the Davis Score Card for organoleptic analysis. Wines from red Hybrid 18/10 possessed phenolic content of 2097mg/l, had a brilliant colour and sensory score of 13.1. Hybrid 23/2 gave good quality white, dry table wines with a sensory score of 13.4.